Desenvolvimento de um jogo mobile para promover a preservação do boto na Região Amazônica - RIBEIRO, Jéssica de Paula Figueira (2019)
The river dolphins are animals found in rivers of the Amazon region and are part of the culture and are present in the day-to-day lives of riverside communities. However, there are legends and beliefs related to river dolphins, which end up putting its different species in danger. This work aimed to develop a mobile version of an educational game to be used in the education and awareness of children from riverside areas, where the presence of river dolphins is common. The existence of a mobile version of the game makes its distribution easier and increases its reach, making it possible to be used outside the classrooms. The game, titled Jogo do Boto presents general knowledge about the life of the river dolphin and promotes environmental awareness about the Amazonian culture. The application was developed using the Unity game engine and a Short Game Design Document for Digital Educational Games (SGDDEdu) was elaborated, describing the gameplay and essential elements of the game. The methodological model used to develop the game is an interactive model that brings together the positive characteristics of different game development and design models to deliver a quality game, following the best existing practices. Software quality and functionality tests were performed, the defects found during the tests were corrected and usability improvements were made, to improve the player's experience. The game proved to be a tool capable of transmitting knowledge, in a playful and fun way, bringing real information about the river dolphins, with the goal of allying local ecological knowledge with scientific knowledge, developing a sense of conservation and appreciation of fauna, flora and the environment.